Antidepressant Effects of Cleistocalyx nervosum Extract Consumption in a Rat Model of Post Stroke Depression - Wathita Phachonpai (Journal of Global Pharma Technology, 2020)
The aim of this study was designed to evaluate whether Cleistocalyx nervosum (C. nervosum) extract improved depression-like behaviors induced by middle cerebral artery occlusion (MCAO) in post-stroke-depression (PSD) rats. Right MCAO procedure was performed on day 1 in male Wistar rats. C. nervosum was thereafter administered (250, 500 and 750 mg/kg), daily for 28 days. Neurological functions after ischemia were determined by the forelimb grip force and the hot plate tests. Tail suspension (TST) and forced swimming (FST) tests were used to assess depression-like symptoms. Plasma corticosterone (CORT) level, and brain oxidative status, and scavenging enzymes were also investigated. Our results showed that three doses of C. nervosum treatment were able to diminish neurological impairments and exert antidepressant effects in PSD rats. This was accompanied by the decrease in stress hormone level and brain oxidation indices, and increase in antioxidant enzymes activities. It suggested that C. nervosum could improve the depression-like emotional status and promote recovery of motor and sensory functions in PSD, and can be applied as a complementary agent for treatment of PSD.